Development of corn starch based composite edible coating for (solanum melongena) brinjal. - CHANDUKISHORE.T; MAHESH KUMAR.M; DR. PERIYAR S SELVAM (International Journal of Pharma and Bio Sciences, 2018)
The purpose of this work is to design a corn starch based composite edible coating for eggplant to improve its shelf life and to study the change in different physical & chemical parameters for concentration variants of Cornstarch like 2%, 2.5%, and 3% coatings which are stored at ambient temperature. High amylose starches have many applications in formation of films, gels, candies and also coatings when exposed to heat at 60°C and above temperature conditions. Corn starch with high amylose exhibits gelatinization property at above 90ºC temperatures. Monolaurin an active component present in Coconut oil exhibits pronounced antifungal property. Coconut oil which is also used as carrier oil for Cinnamon oil- combination of these oils acts as lipid component of composite coating showed a combined effect of gas and water barrier for egg plants. Comparing different concentration level of cornstarch, 2.5% concentration showed more promising effect with more reduced weight loss, firmness loss, moisture loss and reduction in gradual increase of TSS, and reduction in color loss parameters. Overall analysis of physical and chemical parameters shows that TSS, Phenolic Content, pH, moisture loss, colour loss and weight loss were gradually increasing for both coated and control samples but, coated samples were comparatively good in all aspects of parameters analysed during storage days for 12 days at ambient temperature.